Roar of the Lion in the Literary Jungles of Nusantara (Malay Literature, 2014)
This article highlights the connection between Malay literature in Singapore and the literature of Malaysia and other nations of Nusantara, the Malay world. It examines effects of the political separation of 9 August 1965 on Malay literature in Singapore. Has separation of almost 50 years truly severed ties between Malaysia and Singapore as far as Malay literature is concerned? Do Malay literary works reflect a divide between the cultures of Malaysia and Singapore? Is there still continuity in the spirit of a common origin? This article attempts to answer these questions through discussion on the developments in a shared literature before 1965, effects and themes of "separation" in the literary works, phases in the development of literature since 1965, as well as patterns of literary connection between Malaysia and Singapore.Keywords: Malay literature in Singapore, classical Malay literature, literary bonds, political separation, roar of the lion, jungles of Nusantara, spirit of common origin